2015
DOI: 10.1080/10942912.2015.1071840
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Cocoa Beans (Theobroma cacao L.): Influence of Cultivar and Roasting Conditions

Abstract: Effects of various roasting conditions on antioxidant properties of five Theobroma cacao L.varieties were investigated. The cocoa beans were roasted at four different temperatures (110-150°C) and three different air humidities (0.3-5.0%). The raw cocoa beans were characterized by high antioxidant activities. The antioxidant properties of the roasted cocoa beans varied markedly among the analyzed cultivars and geographical regions and were affected by roasting conditions. Generally, cocoa beans of the cv. Foras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
3
37
1
1
Order By: Relevance
“…The roasting effect on the antioxidative properties of cocoa beans depends on the comparative amounts of thermal degradation of naturally occurring phenolic compounds and the introduction of new antioxidants like Maillard reaction products and polymeric pigments. Oracz and Nebesny [75] demonstrated that low-temperature heat treatment with moist air may be used to increase contents of phenols and antioxidative activity of roasted cocoa beans. Study results prove cocoa beans to be a positive source of antioxidants after roasting.…”
Section: Roastingmentioning
confidence: 99%
“…The roasting effect on the antioxidative properties of cocoa beans depends on the comparative amounts of thermal degradation of naturally occurring phenolic compounds and the introduction of new antioxidants like Maillard reaction products and polymeric pigments. Oracz and Nebesny [75] demonstrated that low-temperature heat treatment with moist air may be used to increase contents of phenols and antioxidative activity of roasted cocoa beans. Study results prove cocoa beans to be a positive source of antioxidants after roasting.…”
Section: Roastingmentioning
confidence: 99%
“…Roasting is a rapid processing method that enhances the oxidative and tocopherol stability, antioxidant attributes, and amounts of saturated fatty acids in oils. [6][7][8][9] However, microwave processing of foods is a recent development, which is gaining momentum in household as well as large-scale food applications. [10] Recent studies suggest that through microwave exposure of seeds, greater amount of bioactive compounds may penetrate into the produced oil.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the addition of carob powder increased the antiradical properties of muffins. The total antiradical activity of carob powder increased during roasting [ 22 ], while the antiradical properties of roasted cocoa beans varied significantly among the cultivars and geographical regions and were affected by roasting conditions [ 8 ]. These factors could influence the antiradical properties of carob and cocoa powders.…”
Section: Resultsmentioning
confidence: 99%
“…Cocoa powder is one of the most popular additives in bakery industry due to its unique flavor and properties. Cocoa polyphenols have been described as bioactive compounds with antioxidant and anticarcinogenic properties [ 7 , 8 ]. It was proved that cocoa powder and dark chocolate may positively affect cardiovascular disease (CVD) risk status by modestly reducing LDL-cholesterol (low density lipoprotein) oxidation susceptibility, increasing serum total antioxidant capacity and HDL-cholesterol (high density lipoprotein) concentrations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%